The Pivotal Role of Management Control in Times of Crisis: Enhancing Organizational Resilience and Strategic Adaptation - Snoussi, Nabila; Elhamma, Azzouz (European Scientific Journal, ESJ, 2025)
This article examines the transformation of management control, which has traditionally been regarded as a support function, into a central strategic lever in times of crisis. The study is focused on three core areas: the impact of management control mechanisms on organisational performance; their role in facilitating adaptation in a crisis context; and the influence of adopting new control tools on the company’s strategic direction. The research utilises a quantitative approach and is based on a sample of 97 companies across various sectors and sizes, ensuring diverse representation via non-stratified random sampling. Statistical techniques employed include Wilcoxon Signed-Rank Tests, quantile regression, and Spearman’s correlation coefficients to validate the hypotheses. The findings demonstrate that management control is a key factor in enhancing performance, organisational resilience, and the implementation of a proactive strategy. Specifically, advanced technologies such as artificial intelligence (AI) and enterprise resource planning (ERP) systems were shown to enable companies to anticipate risks, seize opportunities, and strengthen their competitive advantage during crises. However, several limitations remain. These include the relatively small sample size, which restricts generalizability, the specific nature of the crises under study (COVID-19 crisis) and the potential for respondent bias, as most participants were senior executives or management controllers. These factors highlight the need for further research, particularly the exploration of additional crisis contexts and the use of mixed methodologies for a more comprehensive analysis.